Life cycle assessment and life cycle cost of tofu production and its extended recycling scenario - S. Hartini; A.N. Fatliana; N.U. Handayani; P.A. Wicaksono; B.S. Ramadan; T. Matsumoto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The current literature on tofu production has predominantly focused on exploring the value-added potential of the waste generated during tofu production and conducting impact assessments related to this production. However, a noticeable gap remains in the research concerning the comprehensive examination of life cycle costs and eco-efficiency in tofu production and its associated waste. This study aims to assess the environmental and economic impacts of the implementation of recycling alternatives using a life cycle assessment and life cycle cost approach. The impact of waste recycling on the eco-efficiency of small and medium-sized enterprises in Sugihmanik Village, Grobogan Regency, Indonesia is also examined.METHODS: To achieve this goal, this study employed life cycle assessment and life cycle cost methodologies to evaluate eco-efficiency. Data were collected through interviews and direct observations. Cradle-to-grave (tofu production) and cradle-to-cradle (tofu production and waste recycling) approaches were compared. Environmental impact was assessed by determining the 12 impact categories. Environmental cost was determined using the eco-cost 2023 method, and environmental and economic impacts were examined with SimaPro software version 9.4.FINDINGS: Life cycle assessment analysis revealed eutrophication, carbon footprint, and freshwater ecotoxicity to be the categories with the most significant impact for each process. In particular, the eco-cost of the cradle-to-grave approach was 7.03 United States dollars, and that of the cradle-to-cradle approach was 7.90 United States dollars. Life cycle cost analysis yielded a net value of 1.33 United States dollars for the cradle-to-grave process and 38.16 United States dollars for the cradle-to-cradle process. According to the life cycle cost analysis, the recycling scheme increased the overall cost of production. Meanwhile, the eco-efficiency analysis demonstrated an increase in the eco-efficiency of tofu production (cradle-to-grave) and the recycling system (cradle-to-cradle). Waste recycling can increase the eco-efficiency index from 0.18 to 5.CONCLUSION: Life cycle assessment identified eutrophication, carbon footprint, and ecotoxicity (freshwater) as the three major impact categories. Proper waste management in tofu production offers environmental benefits and significant profits, with the net value of the cradle-to-cradle process at 38.99 US dollars. The eco-efficiency values showed a substantial positive increase, and the waste processing scenarios were found to be sustainable and economically beneficial. These findings suggest new business opportunities through straightforward waste processing and affordable production costs. The scheme also reduces the environmental impact and increases the efficiency and profit of the overall tofu production system.